Analisis Pengungkapan Sustainability Reports Berdasarkan Gri Standards 300: Sektor Basic Materialis (Pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2024) - Dea Natalia Purba; Naina Azzahra Heraman (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study aims to analyze the level of disclosure in sustainability reports based on GRI Standards 300 in companies in the Basic Materials sector listed on the Indonesia Stock Exchange (IDX) in 2024. The research method used is a documentation method by analyzing the sustainability reports and/or annual reports of companies. The level of disclosure is measured based on GRI 300 indicators that cover key environmental aspects. The results show that 77% of companies have fully disclosed GRI 300 indicators, while 23% of companies have not disclosed these aspects, and no companies were found to have partially disclosed them. These findings indicate that the level of disclosure tends to be dichotomous. Based on legitimacy theory, disclosure is carried out as an effort by companies to maintain social legitimacy. Meanwhile, according to stakeholder theory, disclosure reflects the company's response to stakeholder demands for environmental transparency. This study concludes that although the level of disclosure is relatively high, there is still a gap in the implementation of sustainability reporting in the Basic Materials sector.